The South Texas Health Status Review A Health Disparities Roadmap - Ramirez, Amelie G.; Thompson, Ian M.; Vela, Leonel. (Springer International Publishing : Imprint: Springer, 2013)
A Health Disparities Roadmap: The South Texas Health Status Review Edited by Amelie G. Ramirez, Ian M. Thompson, and Leonel Vela As America's most populous state goes, so goes the nation. And within that state, the 38 counties comprising South Texas--a highly populated, largelyHispanicarea characterized by high uninsured rates and low numbers of health care providers--are emblematic of nationwide crises in public health. The South Texas Health Status Review: A Health Disparities Roadmapbrings health care disparities to light in instructive detail. Over thirty key health conditions and risk factors, such as breast cancer, diabetes, obesity, tuberculosis, smoking and alcohol use, lead exposure, birth defects, and homicide rates, are analyzed by age, sex, race/ethnicity, and location (urban or rural), and the results compared with the rest of Texas and the nation as a whole. A section on conclusions and recommendations outlines factors contributing to these conditions and offers suggestions for improvement. These important data should stimulate further population studies and provide impetus for targeted public health interventions and community outreach programs to reduce health inequities and advance care access in the state and the U.S. at large. Major health issues covered in the report include: Communicable diseases Cancer incidence and mortality Maternal and child health Chronic diseases Behavioral risk factors in adults Environmental health issues Suicide, homicide, and vehicular mortality The South Texas Health Status Reviewcontains valuable lessons for researchers in health promotion and health disparities, as well as community health professionals. Policymakers involved in reducing health disparities will find it especially useful.